The impact of calorie labelling and proportional pricing on out of home food orders: a randomised controlled trial study using a virtual food and drink delivery app - Amy Finlay; Emma Boyland; Andrew Jones; Rozemarijn Witkam; Eric Robinson (International Journal of Behavioral Nutrition and Physical Activity, 2023)
Abstract Background Mandatory calorie labelling in the out-of-home food sector was introduced in England in 2022, and menu pricing strategies that ensure cost is equivalent to portion size (proportional pricing) have been proposed as a policy to reduce obesity. Food delivery app-based platforms now contribute significantly to diet, and evidence suggests that those at a socioeconomic disadvantage may have greater exposure to unhealthy options on these platforms. However, public health policies to improve nutritional quality of food ordered from food delivery apps has received limited examination. Objective This experimental study assessed the impact of calorie labelling and proportional pricing on item and meal size selection, calories ordered, and money spent when selecting food and drinks from three outlet types on a virtual delivery app. Methods UK adult participants (N = 1126, 49% female), stratified by gender and education level completed an online study where they ordered items from three branded food and beverage outlets (coffee shop, sandwich outlet, fast food outlet) using a virtual delivery app. Participants were presented food and beverage options with vs. without calorie labels and with value (larger portions are proportionally cheaper) vs. proportional pricing. Results Calorie labelling did not influence portion size selection for any outlets, but significantly reduced calories ordered from the coffee shop (-18.95kcals, 95% CI -33.07 to -4.84) and fast food outlet (-54.19kcals, 95% CI -86.04 to -22.33). Proportional pricing reduced the likelihood of choosing a larger beverage from the coffee shop (OR = 0.58, 95% CI 0.45 to 0.75), but was associated with increased calories ordered from the fast food outlet (51.25kcals, 95% CI 19.59 to 82.90). No consistent interactions were observed with participant characteristics, suggesting that effects of calorie labelling and pricing on outcomes were similar across sociodemographic groups. Conclusions Calorie labelling on food delivery platforms may effectively reduce calories ordered. Proportional pricing may be useful in prompting consumers to select smaller portion sizes, although further research in real-world settings will now be valuable.